2017
DOI: 10.18632/oncotarget.23388
|View full text |Cite
|
Sign up to set email alerts
|

A dual mechanism of activation of the Sonic Hedgehog pathway in anaplastic thyroid cancer: crosstalk with RAS-BRAF-MEK pathway and ligand secretion by tumor stroma

Abstract: Sonic Hedgehog (Shh) pathway regulates embryonic development of different organs including the thyroid gland. The aberrant activation of Shh signaling has been found in several types of cancer and according to recent evidences it represents an important regulator of tumor-stroma interaction. In this study, we have analyzed expression, activation and molecular mechanisms regulating the Shh pathway and its involvement in the modulation of tumor stroma interaction in anaplastic thyroid cancer (ATC) cells. Our res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 38 publications
1
14
0
1
Order By: Relevance
“…The most common structural aberration, gain/ amplification of the fragment of the chromosome 12p, was present in 3/13 samples. None of the other CNAs either observed in our study or reported previously was seen consistently [19,23,36,45]. In the previously published pilot study [25], we have identified only two recurrent aberrations, namely gains at 12p13.33p11.1 and 17q11.1q25.3.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…The most common structural aberration, gain/ amplification of the fragment of the chromosome 12p, was present in 3/13 samples. None of the other CNAs either observed in our study or reported previously was seen consistently [19,23,36,45]. In the previously published pilot study [25], we have identified only two recurrent aberrations, namely gains at 12p13.33p11.1 and 17q11.1q25.3.…”
Section: Discussionsupporting
confidence: 59%
“…These include overexpression of SMO, GLI1 and other regulatory enhancers or decreased/ silenced expression or aberrant function of PTCH1, SUFU, and cooperating repressors. Important in oncogenic signalling are crosstalks with transforming growth factor β (TGF-β)/BMP, WNT, Hippo, EGFR, K-Ras, PKA, Notch, PKC, Mek1, GSK3B, PI3K and other systems [19,35,36]. Therefore, a whole-genome screening approach with using the microarray-CGH technique was applied in the current report to evaluate the signs of alterations at various points of the pathway in the examined group of intracranial paediatric GCTs.…”
Section: Discussionmentioning
confidence: 99%
“…Female mice seem to be more sensitive towards the effect of Hh signalling in terms of energy metabolism. These findings should be considered, as therapeutic treatments targeting the Hh pathway seem to be a promising therapy for different cancer types [54,55]. The sex-specific effect of Hh inhibitors on energy metabolism could make a difference in the survival of male and female patients, which is often reduced by aggressive therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the expression of GLIs could be regulated through a SMO-independent pathway. A series of factors such as oncogenic receptor tyrosine kinases, RAS/MAP kinase, PI3K/AKT/S6K, DYRK1A, PKC, TGF-β, and histone deacetylases could enhance the transcriptional activity of GLIs in human cancer cells 34,35 . It was well documented that TGF-β always acted as a key player in epithelial–mesenchymal transition (EMT)-mediated tumor metastasis and therapy resistance in LUADs, which might be the likely mediator to modulate the transcription of GLIs 36 .…”
Section: Discussionmentioning
confidence: 99%